Waterproof coating and preparation method thereof
By introducing ketone carbonyl and amino groups into sheet hydrotalcite, and modifying hydrotalcite with components such as bisacetone acrylamide and 2-aminoethyl methacrylate to form a tight network structure, the problem of insufficient waterproof performance of traditional waterproof coatings is solved, and the waterproof and mechanical properties of the coating are significantly improved.
Patent Information
- Application Number
- CN202510283505.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-22
AI Technical Summary
Traditional waterproof coatings have defects in waterproof performance. The moisture can penetrate through the micropores and defects of the coating, resulting in a decrease in waterproofing effect and cannot meet the needs of buildings and facilities for long-term stable waterproof protection.
By introducing ketone carbonyl and amino groups into sheet hydrotalcite, the precise control of the crosslink density of the coating system is achieved. Hydroxytalcite is modified by using components such as bisacetone acrylamide and 2-aminoethyl methacrylate to form a tighter network structure to enhance the waterproofing and mechanical properties of the coating.
It significantly improves the waterproof performance and mechanical strength of the coating, forms a dense network structure, effectively prevents moisture penetration, and meets the needs of buildings and facilities for long-term stable waterproof protection.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a waterproof coating and a preparation method thereof. Background Art
[0002] Waterproof coatings are important functional materials used to prevent water from penetrating the surface of objects and protect objects from water erosion. In recent years, with the continuous advancement of various infrastructure construction and the vigorous development of the construction industry, people's requirements for building quality and durability have been increasing. As a key material to ensure the waterproof performance of buildings, the performance of waterproof coatings has also received more and more attention.
[0003] After the traditional coating is formed into a film, its internal microstructure has many pores and defects that cannot be ignored. The existence of these microscopic pores and defects is like a series of hidden "channels", providing convenient conditions for the penetration of water. Even under normal water pressure, water can penetrate into the interior of the coating through these tiny channels. This penetration process seems slow, but it will continuously weaken the waterproof effect of the coating, causing holes in the waterproof barrier that should have been tight, thereby reducing the overall waterproof performance.
[0004] With the continuous progress of society, the durability requirements for buildings and various facilities are getting higher and higher. Whether it is residential buildings, commercial buildings or industrial facilities, waterproof coatings are required to provide long-term and stable waterproof protection. Therefore, the development of a new waterproof coating that can overcome the shortcomings of traditional waterproof coatings in terms of waterproof performance has become a key task in the current field, in order to meet the growing market demand and high standards of engineering applications, and ensure the long-term safe use of buildings and facilities. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing a waterproof coating.
[0006] A method for preparing a waterproof coating comprises the following steps: S1, dispersing the flaky hydrotalcite in anhydrous ethanol, ultrasonicating, adding vinyltrimethoxysilane, stirring in a constant temperature water bath, filtering, washing, and drying to obtain olefinated hydrotalcite; S2. Disperse olefinated hydrotalcite, diacetone acrylamide and 2-aminoethyl methacrylate in anhydrous ethanol under a nitrogen atmosphere, stir, add azobisisobutyronitrile, stir in a constant temperature water bath, filter, wash and dry to obtain modified flaky hydrotalcite; S3, polytetrahydrofuran diol and isophorone diisocyanate are mixed, stirred in a constant temperature water bath under a nitrogen atmosphere, dibutyltin dilaurate is added, stirred in a constant temperature water bath, 2,2-dimethylolpropionic acid and adipic acid dihydrazide are added, stirred, triethylamine and deionized water are added, stirred to obtain a hydrazide-modified polyurethane emulsion; S4. Add the modified flaky hydrotalcite to the hydrazide-modified polyurethane emulsion, stir, add a dispersant and a defoaming agent, stir, and obtain a waterproof coating.
[0007] Preferably, in step S1, the weight ratio of the flaky hydrotalcite to the vinyltrimethoxysilane is 8-12:1-2.
[0008] Preferably, in step S1, the flaky hydrotalcite is dispersed in anhydrous ethanol and then subjected to ultrasonic treatment, the ultrasonic time is 20-40 min, and the ultrasonic frequency is 40-50 kHz.
[0009] Preferably, in step S1, after adding vinyltrimethoxysilane, the mixture is stirred in a constant temperature water bath, the water bath temperature is 55-65° C., the stirring time is 3-4 h, and the stirring speed is 200-300 rpm.
[0010] Preferably, in step S1, the drying temperature is 78-82° C. and the drying time is 5-6 hours.
[0011] Preferably, in step S2, the weight ratio of olefinated hydrotalcite, diacetone acrylamide, 2-aminoethyl methacrylate and azobisisobutyronitrile is 8-12: 1-3: 2-4: 0.1-0.3.
[0012] Preferably, in step S2, olefinated hydrotalcite, diacetone acrylamide and 2-aminoethyl methacrylate are dispersed in anhydrous ethanol and then stirred for 0.5-1 h at a stirring speed of 200-300 rpm.
[0013] Preferably, in step S2, after adding azobisisobutyronitrile, stirring is carried out in a constant temperature water bath, the water bath temperature is 68-72° C., the stirring time is 5-6 h, and the stirring speed is 100-200 rpm.
[0014] Preferably, in step S2, the drying temperature is 58-62° C. and the drying time is 10-14 h.
[0015] Preferably, in step S3, the weight ratio of polytetrahydrofuran diol, isophorone diisocyanate, dibutyltin dilaurate, 2,2-dihydroxymethylpropionic acid, adipic acid dihydrazide and triethylamine is 15-25: 6-10: 0.1-0.3: 0.5-0.7: 2-3: 0.4-0.5.
[0016] Preferably, in described step S3, the molar mass of polytetrahydrofuran diol is 1000-1800g / mol.
[0017] Preferably, in step S3, after polytetrahydrofuran diol and isophorone diisocyanate are mixed, they are stirred in a constant temperature water bath under a nitrogen atmosphere, the water bath temperature is 50-60° C., the stirring time is 10-20 min, and the stirring speed is 200-300 rpm.
[0018] Preferably, in step S3, after adding dibutyltin dilaurate, stirring is carried out in a constant temperature water bath, the water bath temperature is 80-90° C., the stirring time is 3-4 h, and the stirring speed is 200-300 rpm.
[0019] Preferably, in step S3, 2,2-dihydroxymethylpropionic acid and adipic acid dihydrazide are added and then stirred for 2-3 hours at a stirring speed of 200-300 rpm.
[0020] Preferably, in step S3, triethylamine and deionized water are added and then stirred for 0.5-1 h at a stirring speed of 200-300 rpm.
[0021] Preferably, in step S4, the weight ratio of the modified flaky hydrotalcite, the hydrazide-modified polyurethane emulsion, the dispersant and the defoaming agent is 3-7:90-110:0.5-1:0.3-0.4.
[0022] Preferably, in step S4, the modified flaky hydrotalcite is added to the hydrazide-modified polyurethane emulsion and then stirred. The stirring time is 0.5-1 h and the stirring speed is 1000-1200 rpm.
[0023] Preferably, in step S4, the dispersant and defoamer are added and then stirred, the stirring time is 10-20 min, and the stirring speed is 200-300 rpm.
[0024] Preferably, in step S4, the dispersant is BYK-110; and the defoaming agent is BYK-024.
[0025] A waterproof coating is prepared by any of the above-mentioned methods for preparing the waterproof coating. Beneficial Effects
[0026] The present invention achieves precise control of the crosslinking density of the coating system by simultaneously introducing ketocarbonyl and amino groups into the lamellar hydrotalcite, taking into account both waterproof and mechanical properties. This dual crosslinking mechanism not only enhances the mechanical strength of the coating, but also improves its waterproof performance, allowing the coating to form a denser network structure during the curing process, effectively preventing water penetration.
[0027] The introduction of diacetone acrylamide and 2-aminoethyl methacrylate changes the surface properties of hydrotalcite, making it more compatible with polyurethane prepolymer, and helps to evenly disperse hydrotalcite in the coating system to avoid agglomeration. The modified flaky hydrotalcite not only acts as a filler to enhance the mechanical strength of the coating, but also acts as a crosslinking agent, which can more effectively participate in the construction of the crosslinking network and further enhance the overall performance of the coating.
[0028] The modified hydrotalcite and polyurethane prepolymer form an interpenetrating network structure, which increases the entanglement and interaction between molecular chains and improves the waterproof performance of the coating. When the coating is eroded by water, the cross-linked structure and tight molecular arrangement can effectively block the diffusion path of water molecules, thereby ensuring the waterproof effect of the coating. DETAILED DESCRIPTION
[0029] The following lamellar hydrotalcites were purchased from Anhui Wengjia New Material Technology Co., Ltd., model FM308.
[0030] The present invention will be further explained below in conjunction with specific embodiments. Example 1
[0031] A method for preparing a waterproof coating comprises the following steps: S1. Disperse 8 g of flaky hydrotalcite in 90 g of anhydrous ethanol, perform ultrasonic treatment for 20 min at an ultrasonic frequency of 40 kHz, add 1 g of vinyltrimethoxysilane, stir in a constant temperature water bath at 55° C. for 3 h at a stirring speed of 200 rpm, filter, wash, and dry at 78° C. for 5 h to obtain olefinated hydrotalcite; S2. Under a nitrogen atmosphere, 8 g of olefinic hydrotalcite, 1 g of diacetone acrylamide, and 2 g of 2-aminoethyl methacrylate were dispersed in 40 g of anhydrous ethanol, stirred for 0.5 h at a stirring speed of 200 rpm, 0.1 g of azobisisobutyronitrile was added, and stirred in a constant temperature water bath at 68 ° C for 5 h at a stirring speed of 100 rpm, filtered, washed, and dried at 55 ° C for 10 h to obtain a modified flaky hydrotalcite; S3, 15g of polytetrahydrofuran diol with a molar mass of 1000g / mol and 6g of isophorone diisocyanate were mixed, and stirred in a constant temperature water bath at 50°C for 10min under a nitrogen atmosphere at a stirring speed of 200rpm, 0.1g of dibutyltin dilaurate was added, and stirred in a constant temperature water bath at 80°C for 3h at a stirring speed of 200rpm, 0.5g of 2,2-dimethylolpropionic acid and 2g of adipic acid dihydrazide were added, and stirred for 2h at a stirring speed of 200rpm, 0.4g of triethylamine and 30g of deionized water were added, and stirred for 0.5h at a stirring speed of 200rpm to obtain a hydrazide-modified polyurethane emulsion; S4. Add 3 g of modified flaky hydrotalcite to 90 g of hydrazide-modified polyurethane emulsion, stir for 0.5 h at a stirring speed of 1000 rpm, add 0.5 g of dispersant BYK-110 and 0.3 g of defoamer BYK-024, stir for 10 min at a stirring speed of 200 rpm, and obtain a waterproof coating. Example 2
[0032] A method for preparing a waterproof coating comprises the following steps: S1. Disperse 12 g of flaky hydrotalcite in 110 g of anhydrous ethanol, perform ultrasonic treatment for 40 min at an ultrasonic frequency of 50 kHz, add 2 g of vinyltrimethoxysilane, stir in a constant temperature water bath at 65° C. for 4 h at a stirring speed of 300 rpm, filter, wash, and dry at 82° C. for 6 h to obtain olefinated hydrotalcite; S2. Under a nitrogen atmosphere, 12 g of olefinic hydrotalcite, 3 g of diacetone acrylamide, and 4 g of 2-aminoethyl methacrylate were dispersed in 60 g of anhydrous ethanol, stirred for 1 h at a stirring speed of 300 rpm, 0.3 g of azobisisobutyronitrile was added, and stirred in a constant temperature water bath at 72 ° C for 6 h at a stirring speed of 200 rpm, filtered, washed, and dried at 65 ° C for 14 h to obtain a modified flaky hydrotalcite; S3, 25g of polytetrahydrofuran diol with a molar mass of 1800g / mol and 10g of isophorone diisocyanate were mixed, and stirred in a constant temperature water bath at 60°C for 20min under a nitrogen atmosphere at a stirring speed of 300rpm, 0.3g of dibutyltin dilaurate was added, and the mixture was stirred in a constant temperature water bath at 90°C for 4h at a stirring speed of 300rpm, 0.7g of 2,2-dimethylolpropionic acid and 3g of adipic acid dihydrazide were added, and the mixture was stirred for 3h at a stirring speed of 300rpm, 0.5g of triethylamine and 50g of deionized water were added, and the mixture was stirred for 1h at a stirring speed of 300rpm to obtain a hydrazide-modified polyurethane emulsion; S4. Add 7 g of modified flaky hydrotalcite to 110 g of hydrazide-modified polyurethane emulsion, stir for 1 h at a stirring speed of 1200 rpm, add 1 g of dispersant BYK-110 and 0.4 g of defoamer BYK-024, stir for 20 min at a stirring speed of 300 rpm, and obtain a waterproof coating. Example 3
[0033] A method for preparing a waterproof coating comprises the following steps: S1. Disperse 10 g of flaky hydrotalcite in 100 g of anhydrous ethanol, perform ultrasonic treatment for 30 min at an ultrasonic frequency of 45 kHz, add 1.5 g of vinyltrimethoxysilane, stir in a constant temperature water bath at 60° C. for 3.5 h at a stirring speed of 250 rpm, filter, wash, and dry at 80° C. for 5.5 h to obtain olefinated hydrotalcite; S2. Under a nitrogen atmosphere, 10 g of olefinic hydrotalcite, 2 g of diacetone acrylamide, and 3 g of 2-aminoethyl methacrylate were dispersed in 50 g of anhydrous ethanol, stirred for 0.75 h at a stirring speed of 250 rpm, 0.2 g of azobisisobutyronitrile was added, stirred in a constant temperature water bath at 70 ° C for 5.5 h at a stirring speed of 150 rpm, filtered, washed, and dried at 60 ° C for 12 h to obtain a modified flaky hydrotalcite; S3, 20g of polytetrahydrofuran diol with a molar mass of 1400g / mol and 8g of isophorone diisocyanate were mixed, and stirred in a constant temperature water bath at 55°C for 15min under a nitrogen atmosphere at a stirring speed of 250rpm, 0.2g of dibutyltin dilaurate was added, and stirred in a constant temperature water bath at 85°C for 3.5h at a stirring speed of 250rpm, 0.6g of 2,2-dimethylolpropionic acid and 2.5g of adipic acid dihydrazide were added, and stirred for 2.5h at a stirring speed of 250rpm, 0.45g of triethylamine and 40g of deionized water were added, and stirred for 0.7h at a stirring speed of 250rpm to obtain a hydrazide-modified polyurethane emulsion; S4. Add 5 g of modified flaky hydrotalcite to 100 g of hydrazide-modified polyurethane emulsion, stir for 0.75 h at a stirring speed of 1100 rpm, add 0.75 g of dispersant BYK-110 and 0.35 g of defoamer BYK-024, stir for 15 min at a stirring speed of 250 rpm, and obtain a waterproof coating.
[0034] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that vinyltrimethoxysilane is not used to graft the flaky hydrotalcite; A method for preparing a coating comprises the following steps: S1. Under a nitrogen atmosphere, 10 g of flaky hydrotalcite, 2 g of diacetone acrylamide, and 3 g of 2-aminoethyl methacrylate were dispersed in 50 g of anhydrous ethanol, stirred for 0.75 h at a stirring speed of 250 rpm, 0.2 g of azobisisobutyronitrile was added, stirred in a constant temperature water bath at 70 ° C for 5.5 h at a stirring speed of 150 rpm, filtered, washed, and dried at 60 ° C for 12 h to obtain a modified flaky hydrotalcite; S2, 20g of polytetrahydrofuran diol with a molar mass of 1400g / mol and 8g of isophorone diisocyanate were mixed, stirred in a constant temperature water bath at 55°C for 15min under a nitrogen atmosphere at a stirring speed of 250rpm, 0.2g of dibutyltin dilaurate was added, and stirred in a constant temperature water bath at 85°C for 3.5h at a stirring speed of 250rpm, 0.6g of 2,2-dimethylolpropionic acid and 2.5g of adipic acid dihydrazide were added, and stirred for 2.5h at a stirring speed of 250rpm, 0.45g of triethylamine and 40g of deionized water were added, and stirred for 0.7h at a stirring speed of 250rpm to obtain a hydrazide-modified polyurethane emulsion; S3. Add 5 g of modified flaky hydrotalcite to 100 g of hydrazide-modified polyurethane emulsion, stir for 0.75 h at a stirring speed of 1100 rpm, add 0.75 g of dispersant BYK-110 and 0.35 g of defoamer BYK-024, stir for 15 min at a stirring speed of 250 rpm, and obtain a coating.
[0035] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that: no diacetone acrylamide is added, that is, no keto functional group is introduced into the system; A method for preparing a coating comprises the following steps: S1. Disperse 10 g of flaky hydrotalcite in 100 g of anhydrous ethanol, perform ultrasonic treatment for 30 min at an ultrasonic frequency of 45 kHz, add 1.5 g of vinyltrimethoxysilane, stir in a constant temperature water bath at 60° C. for 3.5 h at a stirring speed of 250 rpm, filter, wash, and dry at 80° C. for 5.5 h to obtain olefinated hydrotalcite; S2. Under a nitrogen atmosphere, 10 g of olefinated hydrotalcite and 3 g of 2-aminoethyl methacrylate were dispersed in 50 g of anhydrous ethanol, stirred for 0.75 h at a stirring speed of 250 rpm, 0.2 g of azobisisobutyronitrile was added, stirred in a constant temperature water bath at 70 ° C for 5.5 h at a stirring speed of 150 rpm, filtered, washed, and dried at 60 ° C for 12 h to obtain a modified flaky hydrotalcite; S3, 20g of polytetrahydrofuran diol with a molar mass of 1400g / mol and 8g of isophorone diisocyanate were mixed, and stirred in a constant temperature water bath at 55°C for 15min under a nitrogen atmosphere at a stirring speed of 250rpm, 0.2g of dibutyltin dilaurate was added, and stirred in a constant temperature water bath at 85°C for 3.5h at a stirring speed of 250rpm, 0.6g of 2,2-dimethylolpropionic acid and 2.5g of adipic acid dihydrazide were added, and stirred for 2.5h at a stirring speed of 250rpm, 0.45g of triethylamine and 40g of deionized water were added, and stirred for 0.7h at a stirring speed of 250rpm to obtain a hydrazide-modified polyurethane emulsion; S4. Add 5 g of modified flaky hydrotalcite to 100 g of hydrazide-modified polyurethane emulsion, stir for 0.75 h at a stirring speed of 1100 rpm, add 0.75 g of dispersant BYK-110 and 0.35 g of defoamer BYK-024, stir for 15 min at a stirring speed of 250 rpm, and obtain a coating.
[0036] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that: 2-aminoethyl methacrylate is not added, that is, amino functional groups are not introduced into the system; A method for preparing a coating comprises the following steps: S1. Disperse 10 g of flaky hydrotalcite in 100 g of anhydrous ethanol, perform ultrasonic treatment for 30 min at an ultrasonic frequency of 45 kHz, add 1.5 g of vinyltrimethoxysilane, stir in a constant temperature water bath at 60° C. for 3.5 h at a stirring speed of 250 rpm, filter, wash, and dry at 80° C. for 5.5 h to obtain olefinated hydrotalcite; S2. Under a nitrogen atmosphere, 10 g of olefinic hydrotalcite and 2 g of diacetone acrylamide were dispersed in 50 g of anhydrous ethanol, stirred for 0.75 h at a stirring speed of 250 rpm, 0.2 g of azobisisobutyronitrile was added, stirred in a constant temperature water bath at 70 ° C for 5.5 h at a stirring speed of 150 rpm, filtered, washed, and dried at 60 ° C for 12 h to obtain a modified flaky hydrotalcite; S3, 20g of polytetrahydrofuran diol with a molar mass of 1400g / mol and 8g of isophorone diisocyanate were mixed, and stirred in a constant temperature water bath at 55°C for 15min under a nitrogen atmosphere at a stirring speed of 250rpm, 0.2g of dibutyltin dilaurate was added, and stirred in a constant temperature water bath at 85°C for 3.5h at a stirring speed of 250rpm, 0.6g of 2,2-dimethylolpropionic acid and 2.5g of adipic acid dihydrazide were added, and stirred for 2.5h at a stirring speed of 250rpm, 0.45g of triethylamine and 40g of deionized water were added, and stirred for 0.7h at a stirring speed of 250rpm to obtain a hydrazide-modified polyurethane emulsion; S4. Add 5 g of modified flaky hydrotalcite to 100 g of hydrazide-modified polyurethane emulsion, stir for 0.75 h at a stirring speed of 1100 rpm, add 0.75 g of dispersant BYK-110 and 0.35 g of defoamer BYK-024, stir for 15 min at a stirring speed of 250 rpm, and obtain a coating.
[0037] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that: diacetone acrylamide and 2-aminoethyl methacrylate are not added, that is, the synergistic regulation effect of acetone acrylamide and 2-aminoethyl methacrylate on the system is not introduced; A method for preparing a coating comprises the following steps: S1. Disperse 10 g of flaky hydrotalcite in 100 g of anhydrous ethanol, perform ultrasonic treatment for 30 min at an ultrasonic frequency of 45 kHz, add 1.5 g of vinyltrimethoxysilane, stir in a constant temperature water bath at 60° C. for 3.5 h at a stirring speed of 250 rpm, filter, wash, and dry at 80° C. for 5.5 h to obtain olefinated hydrotalcite; S2. Under a nitrogen atmosphere, 10 g of olefinic hydrotalcite was dispersed in 50 g of anhydrous ethanol, stirred for 0.75 h at a stirring speed of 250 rpm, 0.2 g of azobisisobutyronitrile was added, stirred in a constant temperature water bath at 70 ° C for 5.5 h at a stirring speed of 150 rpm, filtered, washed, and dried at 60 ° C for 12 h to obtain a modified flaky hydrotalcite; S3, 20g of polytetrahydrofuran diol with a molar mass of 1400g / mol and 8g of isophorone diisocyanate were mixed, and stirred in a constant temperature water bath at 55°C for 15min under a nitrogen atmosphere at a stirring speed of 250rpm, 0.2g of dibutyltin dilaurate was added, and stirred in a constant temperature water bath at 85°C for 3.5h at a stirring speed of 250rpm, 0.6g of 2,2-dimethylolpropionic acid and 2.5g of adipic acid dihydrazide were added, and stirred for 2.5h at a stirring speed of 250rpm, 0.45g of triethylamine and 40g of deionized water were added, and stirred for 0.7h at a stirring speed of 250rpm to obtain a hydrazide-modified polyurethane emulsion; S4. Add 5 g of modified flaky hydrotalcite to 100 g of hydrazide-modified polyurethane emulsion, stir for 0.75 h at a stirring speed of 1100 rpm, add 0.75 g of dispersant BYK-110 and 0.35 g of defoamer BYK-024, stir for 15 min at a stirring speed of 250 rpm, and obtain a coating.
[0038] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that: adipic acid dihydrazide is not added, that is, no hydrazide functional group is introduced into the system; A method for preparing a coating comprises the following steps: S1. Disperse 10 g of flaky hydrotalcite in 100 g of anhydrous ethanol, perform ultrasonic treatment for 30 min at an ultrasonic frequency of 45 kHz, add 1.5 g of vinyltrimethoxysilane, stir in a constant temperature water bath at 60° C. for 3.5 h at a stirring speed of 250 rpm, filter, wash, and dry at 80° C. for 5.5 h to obtain olefinated hydrotalcite; S2. Under a nitrogen atmosphere, 10 g of olefinic hydrotalcite, 2 g of diacetone acrylamide, and 3 g of 2-aminoethyl methacrylate were dispersed in 50 g of anhydrous ethanol, stirred for 0.75 h at a stirring speed of 250 rpm, 0.2 g of azobisisobutyronitrile was added, stirred in a constant temperature water bath at 70 ° C for 5.5 h at a stirring speed of 150 rpm, filtered, washed, and dried at 60 ° C for 12 h to obtain a modified flaky hydrotalcite; S3, 20g of polytetrahydrofuran diol with a molar mass of 1400g / mol and 8g of isophorone diisocyanate were mixed, and stirred in a constant temperature water bath at 55°C for 15min under a nitrogen atmosphere at a stirring speed of 250rpm, 0.2g of dibutyltin dilaurate was added, and stirred in a constant temperature water bath at 85°C for 3.5h at a stirring speed of 250rpm, 0.6g of 2,2-dimethylolpropionic acid was added, and stirred for 2.5h at a stirring speed of 250rpm, 0.45g of triethylamine and 40g of deionized water were added, and stirred for 0.7h at a stirring speed of 250rpm to obtain a modified polyurethane emulsion; S4. Add 5 g of modified flaky hydrotalcite to 100 g of modified polyurethane emulsion, stir for 0.75 h at a stirring speed of 1100 rpm, add 0.75 g of dispersant BYK-110 and 0.35 g of defoamer BYK-024, stir for 15 min at a stirring speed of 250 rpm, and obtain a coating.
[0039] Performance Testing Waterproof performance: The coatings prepared in Examples 1-3 and Comparative Examples 1-5 were uniformly coated on a flat glass sheet, dried and cured to prepare test pieces; the contact angle measuring instrument (Shanghai Zhongchen Digital Technology Equipment Co., Ltd., model JC2000D2) was turned on and preheated; the test piece was horizontally placed on the sample stage of the contact angle measuring instrument, and a micro-syringe was used to generate water droplets on the surface of the test piece. After the droplets were stable, the measuring instrument automatically measured the contact angle value and recorded the data. The results are shown in Table 1.
[0040] Impact strength: According to GB / T 19250-2013 standard, the coatings prepared in Examples 1-3 and Comparative Examples 1-5 were tested for impact strength, and the data were recorded. The results are shown in Table 1.
[0041] Self-repairing performance: According to the T / CSCP 0003-2023 standard, the coatings prepared in Examples 1-3 and Comparative Examples 1-5 were tested for self-repairing performance, and the crack repair rate of the coatings was calculated according to the following calculation formula, and the data was recorded. The results are shown in Table 1.
[0042] Calculation formula: Crack repair rate (%) = ; L 原始 is the original crack length; L 剩余 is the length of the crack after 24 hours.
[0043] Table 1 Performance test results sample Contact angle (°) Impact strength (g·cm) Crack repair rate (%) Example 1 154.8 107.3 97.8 Example 2 154.9 107.5 97.9 Example 3 155.2 108.3 98.3 Comparative Example 1 116.4 85.2 91.2 Comparative Example 2 127.5 92.5 0 Comparative Example 3 132.6 96.3 95.3 Comparative Example 4 122.5 88.2 0 Comparative Example 5 139.2 98.8 0 Data Analysis: From the data of Examples 1-3 in Table 1, it can be seen that the waterproof coating prepared by the present invention has obvious advantages in waterproof performance, mechanical strength and self-repairing performance. Specifically, the average contact angle is about 155°, the highest can reach 155.2°, the average impact strength is about 107.7 g·cm, the highest can reach 108.3 g·cm, the average crack repair rate is 98%, the highest can reach 98.3%, indicating that the comprehensive performance of the coating is extremely superior and stable.
[0044] From the data of Example 3 and Comparative Example 1 in Table 1, it can be seen that in terms of waterproof performance and mechanical strength of the coating, Example 3 is significantly better than Comparative Example 1. This is mainly because after the flaky hydrotalcite is modified by vinyltrimethoxysilane, its surface properties are greatly improved, and it can form a closer combination and a more complete cross-linking structure with other components, effectively fill the existing microscopic pores and gaps, form a more dense network structure, significantly enhance the mechanical strength and self-repairing ability of the coating, block the penetration path of water molecules, and greatly improve the overall performance of the coating.
[0045] From the data of Example 3 and Comparative Examples 2-4 in Table 1, it can be seen that diacetone acrylamide and 2-aminoethyl methacrylate play an important role in improving the waterproof performance and mechanical strength of the coating. This is due to the synergistic effect of diacetone acrylamide and 2-aminoethyl methacrylate. Diacetone acrylamide has a unique molecular structure, and the ketocarbonyl group contained therein provides an important active site for the cross-linking reaction of the coating system. In the film-forming process of the coating, these active sites can react with other components to promote the formation of a cross-linked network, laying the foundation for building a dense waterproof structure. The amino group of 2-aminoethyl methacrylate changes the surface properties of the flaky hydrotalcite, greatly improving the compatibility between the hydrotalcite and the polyurethane prepolymer, helping the hydrotalcite to be evenly dispersed in the coating system and avoiding the occurrence of agglomeration, thereby ensuring the uniformity and integrity of the cross-linked network in the entire coating system, and further enhancing the overall performance of the coating. In addition, since Comparative Examples 2 and 4 do not add diacetone acrylamide and do not introduce keto groups, they do not have self-repairing ability.
[0046] As can be seen from the data of Example 3 and Comparative Example 5 in Table 1, the addition of adipic acid dihydrazide has a crucial impact on the waterproof performance and mechanical strength of the coating. This is because in the construction of the entire coating system, adipic acid dihydrazide participates in the ketohydrazine room temperature self-crosslinking system as a key component, and adipic acid dihydrazide itself has a unique chemical structure, and its hydrazine group can react with the ketocarbonyl of other components in the system. In the coating film forming process, as water and solvent volatilize, the crosslinking reaction is continuously carried out, so that the coating forms a more dense network structure, greatly improving the waterproof performance and mechanical strength of the coating. In addition, since Comparative Example 5 does not add adipic acid dihydrazide, hydrazide groups are not introduced, so it does not have self-repairing ability.
[0047] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing a waterproof coating, characterized in that: The steps include: S1, dispersing the flaky hydrotalcite in anhydrous ethanol, ultrasonicating, adding vinyltrimethoxysilane, stirring in a constant temperature water bath, filtering, washing, and drying to obtain olefinated hydrotalcite; S2. Disperse olefinated hydrotalcite, diacetone acrylamide and 2-aminoethyl methacrylate in anhydrous ethanol under a nitrogen atmosphere, stir, add azobisisobutyronitrile, stir in a constant temperature water bath, filter, wash and dry to obtain modified flaky hydrotalcite; S3, polytetrahydrofuran diol and isophorone diisocyanate are mixed, stirred in a constant temperature water bath under a nitrogen atmosphere, dibutyltin dilaurate is added, stirred in a constant temperature water bath, 2,2-dimethylolpropionic acid and adipic acid dihydrazide are added, stirred, triethylamine and deionized water are added, stirred to obtain a hydrazide-modified polyurethane emulsion; S4, adding the modified flaky hydrotalcite to the hydrazide-modified polyurethane emulsion, stirring, adding a dispersant and a defoaming agent, stirring, and obtaining a waterproof coating; In the step S2, the weight ratio of olefinic hydrotalcite, diacetone acrylamide, 2-aminoethyl methacrylate, and azobisisobutyronitrile is 8-12: 1-3: 2-4: 0.1-0.3; In the step S3, the weight ratio of polytetrahydrofuran diol, isophorone diisocyanate, dibutyltin dilaurate, 2,2-dihydroxymethylpropionic acid, adipic acid dihydrazide, and triethylamine is 15-25: 6-10: 0.1-0.3: 0.5-0.7: 2-3: 0.4-0.5; In the step S4, the weight ratio of the modified flaky hydrotalcite, the hydrazide-modified polyurethane emulsion, the dispersant, and the defoamer is 3-7:90-110:0.5-1:0.3-0.
4.
2. The method for preparing the waterproof coating according to claim 1, characterized in that: In the step S1, the weight ratio of the flaky hydrotalcite to the vinyltrimethoxysilane is 8-12:1-2.
3. The method for preparing the waterproof coating according to claim 1, characterized in that: In the step S1, after adding vinyltrimethoxysilane, the mixture is stirred in a constant temperature water bath, the water bath temperature is 55-65° C., the stirring time is 3-4 hours, and the stirring speed is 200-300 rpm.
4. The method for preparing the waterproof coating according to claim 1, characterized in that: In the step S2, after adding azobisisobutyronitrile, the mixture is stirred in a constant temperature water bath, the water bath temperature is 68-72° C., the stirring time is 5-6 hours, and the stirring speed is 100-200 rpm.
5. The method for preparing the waterproof coating according to claim 1, characterized in that: In the step S3, polytetrahydrofuran diol and isophorone diisocyanate are mixed, and then stirred in a constant temperature water bath under a nitrogen atmosphere, the water bath temperature is 50-60° C., the stirring time is 10-20 min, and the stirring speed is 200-300 rpm.
6. The method for preparing the waterproof coating according to claim 1, characterized in that: In the step S3, dibutyltin dilaurate is added and then stirred in a constant temperature water bath, the water bath temperature is 80-90° C., the stirring time is 3-4 hours, and the stirring speed is 200-300 rpm.
7. A waterproof coating, characterized in that: The waterproof coating is prepared by the preparation method of any one of claims 1 to 6.
Citation Information
Cited By
One-part water-based metallic paint and method for preparing the same
CN122609116A